2011
DOI: 10.3109/0142159x.2011.610840
|View full text |Cite
|
Sign up to set email alerts
|

Peer group reflection helps clinical teachers to critically reflect on their teaching

Abstract: Background: Student evaluations can help clinical teachers to reflect on their teaching skills and find ways to improve their teaching. Studies have shown that the mere presentation of student evaluations is not a sufficient incentive for teachers to critically reflect on their teaching. Aim: We evaluated and compared the effectiveness of two feedback facilitation strategies that were identical except for a peer reflection meeting. Method: In this study, 54 clinical teachers were randomly assigned to two feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 36 publications
4
52
1
Order By: Relevance
“…While well-being has not been an outcome in feedback research within health professions education, research into its effect on learning and performance gives some indication on the conditions in which feedback is perceived as supportive and constructive. A focus on narrative feedback seems important in this context (Boerboom et al 2011;van der Leeuw et al 2013). In short, what is known as high quality feedback within health professions education may equally count as the right kind of feedback that may also improve well-being.…”
Section: Feedback On Performance As a Job Resourcementioning
confidence: 99%
“…While well-being has not been an outcome in feedback research within health professions education, research into its effect on learning and performance gives some indication on the conditions in which feedback is perceived as supportive and constructive. A focus on narrative feedback seems important in this context (Boerboom et al 2011;van der Leeuw et al 2013). In short, what is known as high quality feedback within health professions education may equally count as the right kind of feedback that may also improve well-being.…”
Section: Feedback On Performance As a Job Resourcementioning
confidence: 99%
“…[207][208][209][210][211][212][213][214] Until more research is available to clarify the optimal instructor training methodology, it is suggested that neonatal resuscitation instructors be trained using timely, objective, structured, and individually targeted verbal and/or written feedback (Class IIb, LOE C-EO).…”
Section: Instructors Nrp 867mentioning
confidence: 99%
“…For the critical outcome of improvement in all levels of education or practice, we identified low-quality evidence (downgraded for indirectness and bias) from 5 randomized clinical trial [278][279][280][281][282] enrolling 271 participants (not estimable). Several studies did note at least temporary deterioration in instructor performance after commencement of new instructor training intervention.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…For the important outcome of improvement in instructor performance, we identified very-low-quality evidence (downgraded for indirectness and bias) from 5 randomized clinical trials [278][279][280][281][282] and 2 nonrandomized trials. 283,284 No meaningful numerical summary of the results of these studies could be performed.…”
Section: Consensus On Sciencementioning
confidence: 99%